Propuesta De Modelo Crossdocking Para La Sede De Paquetería Envía Colvanes Bogotá D.C. (2023)
Currently, we are witnessing a series of transformations worldwide that are generating the prevailing need for companies to adapt and reinvent their processes in order to establish themselves solidly and competitively in the market. That is why each of the branches of the business world must undertake the active search for alternatives and strategies that allow them to obtain improvements. significant in achieving their objectives and goals.